Analisis Komponen Lembar Kerja Peserta Didik (LKPD) Biologi Fase E Pada Materi Ekosistem yang digunakan di SMAN 10 Padang: Penelitian - Zhafira; Muhyiatul Fadilah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study was conducted with the aim of analyzing the components of Student Worksheets (LKPD) used in teaching ecosystems in class X E4 of SMA Negeri 10 Padang. This study is a descriptive qualitative study. The methods applied in this study include interviews and document reviews. The instruments used consisted of interview guidelines and document review sheets. Based on the analysis results, it was found that the percentage of completeness of the LKPD components for ecosystems material in class X E4 of SMA Negeri 10 Padang reached 50%. Components that have not been integrated in the LKPD include learning instructions, supporting information, and assessments. The findings of this study indicate that the LKPD used does not meet the ideal compilation components, so revisions are needed to align with the principles of the Independent Curriculum and 21st-century learning.